2016
DOI: 10.1590/1413-785220162405157391
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Risk Factors of Clavicle Fractures in Professional Cyclists

Abstract: Objective:To evaluate the prevalence of clavicle fractures in professional and amateur cyclists and evaluate the factors associated with its occurrence. Method:One hundred and forty professional and amateur athletes were interviewed through a questionnaire regarding age and time practicing bicycling, among others. Results:Among the 140 evaluated cyclists, there were 19 (13.5%) clavicle fractures associated with this sports modality. Conclusion:There was a positive association between time practicing bicycling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…When looking at professional cyclists, collision between cyclists is a common cause of clavicle fracture (39%) followed by collision with obstacles as well as loss of bicycle control with resultant falling [8]. Among 140 amateur and professional cyclists, Nishimi et al [9] correlated the prevalence of clavicular fractures with more intense weekly hour training.…”
Section: Clavicle Epidemiologymentioning
confidence: 99%
“…When looking at professional cyclists, collision between cyclists is a common cause of clavicle fracture (39%) followed by collision with obstacles as well as loss of bicycle control with resultant falling [8]. Among 140 amateur and professional cyclists, Nishimi et al [9] correlated the prevalence of clavicular fractures with more intense weekly hour training.…”
Section: Clavicle Epidemiologymentioning
confidence: 99%
“…Clavicle fractures, 80% of which occur at the midshaft, are the most common injury in cyclists, and studies have reported a prevalence of 13%-16% in this population vs 2.6%-4% in the general population[ 1 - 3 ]. With numerous studies indicating an unsatisfactory outcome and a high nonunion rate following conservative treatment, an increasing trend has been seen toward operative fixation of displaced midshaft clavicle fractures[ 4 ].…”
Section: Introductionmentioning
confidence: 99%